Relationships between parenting practices and perceptions of child behaviour among Korean immigrant mothers and fathers. (18th October 2016) - Lee, Boram; Keown, Louise J.; Brown, Gavin T. L.
Abstract : This study examined parenting styles and culturally‐specific parenting practices of Korean immigrant mothers ( N = 128) and fathers ( N = 79) of children (ages 6–10) in New Zealand and the parenting predictors of child behaviour. Participants completed questionnaires on parenting styles and practices, and parental perceptions of child behaviour. Both parents indicated a high degree of devotion ( Mo jeong ) and involvement in care and education of their child with fathers were more likely than mothers to utilise shaming/love withdrawal and modesty encouragement. Results of regression analyses showed that there were some differences between mothers and fathers in the parenting predictors of child internalising and externalising behaviour problems and prosocial behaviour. Across the whole sample, there were contrasting relationships for authoritative parenting styles, devoted/involved parenting and modesty encouragement/shaming/non‐reasoning parenting practices with child behaviour problems. Results indicated a blend of Western and Korean parenting practices were being utilised after settling in New Zealand.